THE INFLUENCE OF LEADER-MEMBER EXCHANGE, ORGANIZATIONAL CULTURE AND WORK MOTIVATION ON ORGANIZATIONAL COMMITMENT OF MTSN TEACHERS IN NORTH ACEH REGENCY - Dewi, Cut Kumala; Marwan, Marwan; Bahri, Saiful (Jurnal Visipena, 2025)
Teacher organizational commitment is the teacher's desire to remain in the organization, contribute positively, and support the school's goals. This commitment is very important in the context of Indonesian education because it plays a major role in improving the quality of Indonesian education as a whole. The Purpose of this study is to analyze (1) leader-member exchange has a direct influence on organizational commitment in MTsN teachers in North Aceh Regency. (2) organizational culture has a direct influence on organizational commitment in MTsN teachers in North Aceh Regency. (3) work motivation has a direct influence on organizational commitment in MTsN teachers in North Aceh Regency. This study uses a quantitative method, an associative approach, a population of 443 teachers, a sample of 210 teachers, proportional random sampling technique using the Slovin formula at a 5% error rate, a Likert scale questionnaire data collection technique and a path analysis data processing technique. Research findings (1) leader-member exchange has a direct influence on MTsN teacher commitment (2) organizational culture has a direct influence on MTsN teacher commitment (3) work motivation has a direct influence on MTsN teacher commitment. The principal needs to build good relationships with teachers, create a collaborative culture, and provide opportunities for development and fair rewards to improve teacher motivation, commitment, and performance in schools. The principal needs to improve communication, emotional support, a culture of collaboration, and award programs to strengthen the relationship between leader-member exchange, motivation, and teacher commitment in creating better quality education.